2020
DOI: 10.2147/jhl.s265825
|View full text |Cite
|
Sign up to set email alerts
|

<p>Leadership and Management Competencies for Hospital Managers: A Systematic Review and Best-Fit Framework Synthesis</p>

Abstract: Objective Competent managers are vital to the productivity and service quality of healthcare organizations and the sustainability of the healthcare system. To improve their management competence, understanding of management competency requirements is important. The purpose of this study was to synthesize the evidence related to the leadership and management competencies in healthcare organizations through the best-fit method. Methods A systematic review of literature pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
54
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 44 publications
(71 reference statements)
2
54
0
8
Order By: Relevance
“…A systematic review was performed to identify studies focusing on confirming and/or identifying the competency requirements of hospital managers. These competencies include evidence-informed decision-making, operations, administration and resource management, knowledge of health-care environment and the organization, interpersonal, communication qualities and relationship management, leading people and organization, enabling and managing change and professionalism (Kakemam et al, 2020). All of these competencies are consistent with our findings.…”
Section: Discussionsupporting
confidence: 88%
“…A systematic review was performed to identify studies focusing on confirming and/or identifying the competency requirements of hospital managers. These competencies include evidence-informed decision-making, operations, administration and resource management, knowledge of health-care environment and the organization, interpersonal, communication qualities and relationship management, leading people and organization, enabling and managing change and professionalism (Kakemam et al, 2020). All of these competencies are consistent with our findings.…”
Section: Discussionsupporting
confidence: 88%
“…The potential impact of mandated collaboration and hierarchical structuring on trust Other authors in the field have situated interorganisational collaborations as a spectrum from hierarchical relations (i.e. acquisition or merger), through to market relations, in which only price mechanisms bring organisations together temporarily [94]. Our initial review of typologies of healthcare collaborations [29] identified a similar spectrum, defined by the degree of integration in terms of structure and governance, with individual buddying arrangements characterised by low integration and a full merger by high integration [94].…”
Section: Discussionmentioning
confidence: 99%
“…acquisition or merger), through to market relations, in which only price mechanisms bring organisations together temporarily [94]. Our initial review of typologies of healthcare collaborations [29] identified a similar spectrum, defined by the degree of integration in terms of structure and governance, with individual buddying arrangements characterised by low integration and a full merger by high integration [94]. Some readers may consider mergers and acquisitions to not be classified as forms of inter-organisational collaborations due to their mandated nature (from the perspective of the acquired) and intention to unify as a singular entity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…acquisition or merger) through to market relations in which only price mechanisms bring organisations together temporarily (96). Our initial review of typologies of healthcare collaborations (29) identi ed a similar spectrum de ned by the degree of integration in terms of structure and governance with individual buddying arrangements characterised by low integration and a full merger by high integration (96). Some readers may consider mergers and acquisitions to not be classi ed as forms of inter-organisational collaborations due to their mandated nature (from the perspective of the acquired) and intention to unify as a singular entity.…”
Section: Discussionmentioning
confidence: 99%